Decision Making Capability on Knowledge Based Management Information Systems: Perspective from Information Technology and Organizational Commitment - Komar Priatna, Deden; R. Jusdijachlan; Susan Ridwan; Lasminingrat, Anne; Suryani, Herni (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to analyze the influence of Information Technology and Organizational Commitment to Knowledge-based Management Information System and its implication to decision making capability. The target population of this study is comprised of 500 managers and staff members working in construction companies located in the West Java Province. Due to the utilization of SEM-PLS analysis in this study, can utilize the rule of thumb to determine the sample size, which is 20 times the number of parameters present in the research model. Within this study, there are a total of 5 parameters, resulting in a selected sample of 100 managers and staff members. The results of this study found that liquidity, earnings management and independent komisais affect tax aggressiveness, while executive compensation does not affect the aggressiveness of taxes. Based on total adjusted R-Square results prove that liquidity, earnings management, independent commissionist, and executive compensation only affect 26%, while 74% is influenced by other variable not tested in this research.